Descartes e o ceticismo: o estatuto da dúvida na filosofia cartesiana - Maira de Souza Borba (2011)
The object of this dissertation is to analyse the concept of doubt in Descartes, in order to elucidate the roots of its constitution and determine the role played by scepticism in this process. By comparing Descartes with the sceptics, one can conclude that he was influencedmostly by the modern philosophers, his contemporaries (Montaigne, Charron, La Mothe Le Vayer) and that, as to the ancient scepticism, the most important is the distinction between academic and Pyrronian scepticism, which is vital to comprehend the philosopher. Theanalysis of Popkins theory, which is central when trying to determine the role played by skepticism in Descartes philosophy, reveals that there is not enough evidence to validate the idea that Descartes primary aim was to refute scepticism. Nevertheless, one should not underestimate the place occupied by scepticism in Descartes philosophy, for his doubt must be seen as an important step in the search for the truth. It is necessary to point out the fact that scepticism influenced Descartes both in a positive and a negative way. It is by leaving aside one of these aspects that most of the philosophers commentators present radical orinsufficient theories concerning the connection between Descartes and scepticism. To avoid this, one should be attentive to the distinction between academic and Pryrrhonian scepticism, since, while Pyrrhonian scepticism is refused by Descartes, many elements of academicscepticism are assimilated by him.